Empathy In Neurodegenerative Diseases: A Systematic Review - Pick E (Dove Medical Press, 2019)
Emanuele Pick,1 Johann R Kleinbub,1 Stefania Mannarini,1,2 Arianna Palmieri1,3 1Department of Philosophy, Sociology, Education, and Applied Psychology, University of Padova, Padova, Italy; 2Interdepartmental Center for Family Research, University of Padova, Padova, Italy; 3Padova Neuroscience Center, University of Padova, Padova, ItalyCorrespondence: Emanuele PickDepartment of Philosophy, Sociology, Education, and Applied Psychology, University of Padova, Via Venezia, 14, Padova 35131, ItalyTel +39 049 8276696Email emanuele.pick@phd.unipd.itIntroduction: Empathy, in its affective and cognitive components, is a crucial interpersonal ability. It is broadly studied in the field of psychopathology, whereas its study in the neurodegenerative diseases is relatively recent. Existing literature, though, focused on a reduced subset of considered diseases, which often found a compromise in empathy abilities. Organized knowledge about a more comprehensive set of diseases is lacking.Method: The present PRISMA systematic review was aimed at collecting the current available literature concerning empathic alterations in adult patients affected by neurodegenerative diseases. It considered the different empathy components, evaluated existing patterns, the impact on patients’ lives, and treatment considerations.Results: Overall, the 32 retrieved studies describe a spread deterioration of empathic abilities in patients, with each disease displaying its own pattern of empathy functioning. Literature in this field is fragmented and of heterogeneous quality, and further studies are warranted to increase evidence of many preliminary results.Discussion: In conclusion, we highlight the crucial importance of acknowledging empathy deficits in these diseases, showing their repercussion on both patients’ and caregivers’ quality of life, the establishment of a functional doctor–patient relationship, and the development of efficacious psychological intervention. These clinical approaches can be enriched by the knowledge of the spared abilities of patients affected by neurodegenerative diseases.Keywords: neurodegenerative diseases, empathy, mentalizing, doctor-patient relationship, psychological intervention, quality of life